THE PERSPECTIVE OF SECURITY COMMUNICATION IN THE DEMOCRATIC CAMPAIGN FOR THE 2024 GENERAL ELECTION IN INDONESIA - Martasutisna, Raden Ola Triana (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The 2024 Indonesian General Election presents significant challenges, including disinformation, cyber threats, and social polarization, which pose risks to democratic stability. This study aims to analyze security communication in democratic campaigns, focusing on risk mitigation strategies, the role of social media, and cross-sector collaboration. A literature review method was employed, with qualitative descriptive analysis of relevant materials, including journal articles, official reports, and books. Findings reveal that security communication strategies involving early threat detection, the strategic use of social media for credible messaging, and collaboration among governments, media, and civil society effectively enhance public trust. However, challenges such as low digital literacy and information access disparities persist. The integration of big data technology for public conversation analysis offers significant potential for early threat detection and improved communication strategy effectiveness. In conclusion, effective security communication requires inclusive, collaborative, and technology-based approaches to ensure stability and transparency in democratic processes. Keywords: big data, digital literacy, democratic stability, election 2024, security communication